The Fan Study: Intranasal Fentanyl and Inhaled Nitrous Oxide for Fracture Reduction. (1st June 2016) - Hoeffe, J; Trottier, ED; Bailey, B; Shellshear, D; Lagacé, M; Sutter, C; Grimard, G; Cook, R; Babl, FE
Abstract: BACKGROUND: Recently, intranasal (IN) fentanyl and inhaled nitrous oxide/oxygen (N2 O) mixture have been increasingly used for procedural sedation and analgesia (PSA) alone or in combination. There is a lack of data on the efficacy of these combined agents. OBJECTIVES: To evaluate the efficacy of IN fentanyl and N2 O as PSA for the reduction of mildly-to-moderately displaced fractures and dislocations. DESIGN/METHODS: We performed a prospective, observational cohort study between September 2014 and October 2015. Patients were recruited at CHU Sainte Justine (Montréal, Canada) and Royal Children Hospital (Melbourne, Australia). Patients between the age of 4 and 18 years were eligible if PSA consisted of IN fentanyl and N2 O for the reduction of mildly-to-moderately displaced fractures or dislocations. Patients received at least IN fentanyl 1.5 mcg/kg (100 mcg max) and at least a 50/50% mixture of N2 O with oxygen. Primary outcome was the efficacy of PSA measured by the patient assigned Facial Pain Scale-Revised (FPS-R). The Face, Legs, Activity, Cry, Consolability (FLACC) scale was also recorded. Depth of sedation was evalu-ated using the University of Michigan Sedation Scale (UMSS). Adverse events were recorded following the criteria of the Consensus Panel on Sedation Research of PERC/PECARN. Additional data concerning satisfaction or discomfort were evaluated via questionnaires, and follow-up telephone calls were made to elicit information on adverse events after discharge. RESULTS: A total of 91 patients aged 9.7±3.0 years were enrolled. There was no difference between the median FPS-R score during the procedure compared to before: Median 2 and 2 (median difference 0 [95% CI 0, 0]), respectively. The FLACC score was higher during the procedure than before: Median 4 and 0 (median difference 2 [95% CI 1, 3]). UMSS was 1 (95% CI 1, 2) during the procedure. 42 (46%) patients had adverse events, all mild: vertigo (20%), nausea (16%)]or vomiting (12%). A total of 85/88 (97%) parents and 82/85 (96%) ED physicians would want the same sedation in another procedure. CONCLUSION: PSA with IN fentanyl and N2 O seems effective in our cohort study, as evaluated by patient assigned FPS-R. Patients were minimally sedated. Adverse events were frequent but mild. Overall, parents and medical staff would want the same agents used in another procedure. Thus, PSA with IN fentanyl and N2 O appears to be an attractive option for reduction of mildly displaced fractures or dislocations.